DESIGN, MODELLING AND ANALYSIS OF OFF-GRID HYBRID PV-BATTERY-GENSET SYSTEM FOR COMMUNAL LOAD AND ADMINISTRATIVE LOAD UNDER LOAD FOLLOWING CONTROL STRATEGY AT TOMOR VILLAGE, ASMAT, PAPUA - Sahat Halomoan, Yosua
The clean energy transition, environmental policies and the world's increasing demand for electricity, encourage the development of renewable energy technology as a solution for energy sources. Indonesia has great renewable energy potential, especially Solar Energy with an average irradiation of 4.80 kWh/m²/year, but there are still villages that have not yet had electricity access in Papua due to the difficult geographical location. Tomor Village is one of the isolated villages in Asmat Regency, Papua which has an irradiation of 4.65 kWh/m² with a communal load requirement of 34.8 kWh/ day, administrative load on weekdays 11,376 kWh/day and weekend administrative load of 9.3 kWh /day. The potential for irradiation is good enough to implement a hybrid off-grid PLTS system as a power source to meet load requirements. The hybrid system consists of a centralized PV module, boost converter, MPPT with INC algorithm, buck boost converter, battery, DC/AC converter, and genset. In this paper, system design, modelling, simulation and analysis were carried out using MATLAB/Simulink and Homer Pro with a LF dispatch strategy to obtain a techno economic analysis of the system. The results of the analysis were used to implement a reliable hybrid off-grid PV system at clear and cloudy conditions, with economical Levelized Cost of Energy (LCOE), Net Present Cost (NPC) and low emissions from electrical generation.